2009
DOI: 10.4067/s0718-27242009000100003
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of RFID Adoption in Supply Chain among Manufacturing Companies in China: A Discriminant Analysis

Abstract: The growth of China's economy hinges to a large extent on the ability of the industry to operate more efficiently and effectively in the global supply chain system. China's manufacturing companies should pay attention to adopt more efficient supply chain technologies to provide better services for their customers. China has initially carried out research and development and industrialization of technology related to RFID and begun to apply in some areas in recent years. This article studies the determinant fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 13 publications
1
21
0
Order By: Relevance
“…ICT also impacts positively on small business growth, through an increase in productivity (Bassanini and Scarpetta, 2002;Matteucci et al, 2005;Timmer and van Ark, 2005) and sales (Maguire et al, 2007;Ordanini, 2006;Raymond, 2005;Qiang et al, 2006). New technologies also facilitate organisational expansion (Bernadas and Verville, 2005;Matthews, 2007), improve international communications (Raymond et al, 2005) and lead to supply chain improvements (Bayo-Moriones and Lera; Macpherson et al, 2002;Wen et al, 2009). Last, ICT is seen to lead to increased customer satisfaction (Bernadas and Verville, 2005;Yadav and Varadarajan, 2005), improve product quality (Boca and Daraba, 2010) and facilitate the introduction of new products and services (Beccheti et al, 2003;Carlsson, 2004;Hollenstein, 2004).…”
Section: Technological Environmentmentioning
confidence: 99%
“…ICT also impacts positively on small business growth, through an increase in productivity (Bassanini and Scarpetta, 2002;Matteucci et al, 2005;Timmer and van Ark, 2005) and sales (Maguire et al, 2007;Ordanini, 2006;Raymond, 2005;Qiang et al, 2006). New technologies also facilitate organisational expansion (Bernadas and Verville, 2005;Matthews, 2007), improve international communications (Raymond et al, 2005) and lead to supply chain improvements (Bayo-Moriones and Lera; Macpherson et al, 2002;Wen et al, 2009). Last, ICT is seen to lead to increased customer satisfaction (Bernadas and Verville, 2005;Yadav and Varadarajan, 2005), improve product quality (Boca and Daraba, 2010) and facilitate the introduction of new products and services (Beccheti et al, 2003;Carlsson, 2004;Hollenstein, 2004).…”
Section: Technological Environmentmentioning
confidence: 99%
“…IDTechEx forecasts that it is going to rise to $ 27.31 billion in 2024 (Das & Harrop, 2014). The global industry for the RFID technology has been growing steadily since past few years and is expected to grow rapidly before stabilising and settling on a steady growth path (Wen, Zailani & Fernando, 2009).…”
Section: Rfid Implementation: Selectedmentioning
confidence: 99%
“…In the contemporary business environment, the emerging technologies, especially new RFID solutions have provided the security of information management and its application help to develop enterprises in various areas, including members of high-technology clusters. As RFID progresses in its development and application over the next decade, there will be vast opportunities for management researchers to not only study the advancement of this technology, but also to examine its implications from a wide variety of perspectives (Wen, Zailani & Fernando, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…They found that relative advantage, complexity, supply chain integration, and organizational readiness can influence adoption intention. Wen et al (2009) conducted a discriminant analysis of determinants of RFID adoption in supply chain among manufacturing companies in China. Their research revealed that environment characteristics, organizational characteristics, technology as well as product characteristics can influence an organization's intention to adoption RFID technology.…”
Section: Ict Innovation Assimilation In Emerging Countries and Our Unmentioning
confidence: 99%